(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Universal elementary education has been at the centre of attention indiscussions of both democracy and development in the last decade. The focus ofthe education policy must shift from enrolment to improvement in thefunctioning of schools as well as towards raising the quality of educationoutcomes. This paper begins with a consideration of the need for universalizingelementary, and not just primary, education in India. .This paper addressesconcerns of equity, inclusion, and quality in the context of elementaryeducation from the central focus which looks into the dimensions of locationdisadvantage, social exclusion, gender disparity, and special needs forchildren of other neglected groups.